Pengaruh Intensitas Cahaya Matahari Terhadap Proses Perkecambahan Kacang Hijau Pada Media Tanam Kapas - I Ketut Mahardika; Singgih Baktiarso; Fadhiyah Nurul Qowasmi; Aulia Wulansari Agustin; Yesica Listian Adelia (Peneliti.net, 2023)
This research was conducted to review how much impact the intensity of sunlight has on the growth of green bean plants by giving different treatments, namely indoors and outdoors. Where the green beans contained in the room (indoor) do not get sunlight while those outside the room (outdoor) get sunlight. Observations showed that the growth of mung bean plants that did not receive sunlight experienced etiolation (growing rapidly but the stems and leaves were pale in color), while the plants that were outdoors grew slower but had sturdy stems and leaves. This situation is caused by the influence of the auxin hormone, where the hormone cannot work optimally when exposed to sunlight. In plants that are in a dark place the leaves are pale because the plants do not get sunlight so they lack chlorophyll.